A RETROSPECTIVE STUDY ON SEVERITY AND ASSESSMENT OF MEDICATION ERRORS IN A TERTIARY CARE TEACHING HOSPITAL - K, UMAMAHESWARA RAO; ANUHYA P; SUCHARITHA J; SAI KIRAN A (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study mainly aims to assess the severity and occurrence of medication errors (MEs) in a Tertiary Care Teaching Hospital and suggest solutions for reducing MEs. Methods: It is a retrospective study of patients receiving medication during treatment. The techniques used during this study to identify MEs are direct observation of patients, daily review of medication charts by clinical pharmacists, daily audit of prescriptions, and using medication administration records. Results: The study revealed that the majority of MEs fall under the age groups of 51–60 (45), 41–50 (40), 61–70 (31), 31–40 (19), 21–30 (17), 71–80 (16), 81–90(7), 11–20(6), 1–10(3), and 91–100 (1), respectively. Among 185 patients, males were 100 and females were 85, indicating that MEs occurred more in males than females, and the personnel involved in MEs were more nurses than physicians. Conclusion: By assessing the severity and occurrence of MEs, we identified the most common risk factors for the occurrence of MEs. The study concludes that educating nurses, implementing an evidence-based treatment strategy, and fostering communication and collaboration among hospital pharmacists, doctors, and nurses can help to decrease the occurrence of MEs.